(untitled) (Research, Society and Development, 2023)
Objective: This study aimed to describe the intra-hospital transport as practical action to continue the intensive care patient, them related to the activities performed by nurses. Methods: This is a study of integrative review, to search in LILACS, and SciELO BDEnf. Seven articles were reviewed in full where it was able to show that with advance planning the steps of intra-hospital transport becomes possible to minimize the impact of adverse events patient transported in accordance with the resolution at 376 / 2011COFEN. Conclusion: In the analyzed studies not specific references were found regarding the role of nurse during the shipping process itself. It is necessary that further studies be conducted to validate the practice the actual function of the nurse and the importance of their presence during all stages complex and detailed that involve intra-hospital transport to contribute to the quality of care and patient safety.